2000
DOI: 10.1080/003655100750044820
|View full text |Cite
|
Sign up to set email alerts
|

High insulin and low IGF-I plasma levels following pancreas transplantation in rats. Implications for bone and mineral metabolism

Abstract: Primary disturbances in mineral metabolism and deficiencies in insulin and insulin-like growth factor-I (IGF-I) have been implicated in the pathogenesis of diabetic osteopenia. This prompted us to investigate whether normal bone minerals and bone morphology are preserved after pancreas transplantation. To this end, 8 inbred rats (transplants) were compared with 9 sham-operated rats (controls) 20 months after orthotopic pancreas transplantation. While basal levels of insulin remained unaffected by transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…DM can affect bone formation and resorption by creating several metabolic irregularities in calcium-phosphate and acid-base balances. Primary disturbances in vitamin D and mineral metabolisms and a deficiency of insulin and IGF-I have been implicated in the pathogenesis of diabetic bone disease in animal models and IDDM patients [1,2,[17][18][19]. On the other hand, free radicals have been shown to be involved in osteoclastogenesis and in bone resorption [20] and it is thought that diabetes mellitus is associated with increased oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…DM can affect bone formation and resorption by creating several metabolic irregularities in calcium-phosphate and acid-base balances. Primary disturbances in vitamin D and mineral metabolisms and a deficiency of insulin and IGF-I have been implicated in the pathogenesis of diabetic bone disease in animal models and IDDM patients [1,2,[17][18][19]. On the other hand, free radicals have been shown to be involved in osteoclastogenesis and in bone resorption [20] and it is thought that diabetes mellitus is associated with increased oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies by Kissler et al [29,30], using orthotopic pancreas transplantation in rats, have shown that stimulated arterial insulin levels did not vary between controls and transplanted animals 3 months after operation while 20 months after transplantation oral glucose load elicited hyperinsulinemia. Berry et al [31] and Baumgartner et al [32] did not observe any differences in insulin levels after extrinsic pancreatic denervation and partial pancreatectomy in dogs.…”
Section: Discussionmentioning
confidence: 96%